Inducible Clindamycin Resistance Among Community And Hospital Acquired Isolates Of Staphylococcus Species - DR.R.VASANTHI; DR. M.JEYA; MR.KARTHICK (International Journal of Pharma and Bio Sciences, 2012)
The rate of methicillin resistant Staphylococcus aureus (MRSA) infections has increased in recent years and clindamycin is considered to be one of the alternatives in these infections. In our study, a total of 337 Staphylococcus isolates from exudate samples in a tertiary care hospital were tested for inducible clindamycin resistance by D test according to the clinical laboratory standards institute (CLSI) guidelines. The inducible clindamycin resistance was higher 22% in hospital acquired MRSA isolates when compared to 9.8% in community acquired MRSA isolates. All methicillin resistant coagulase negative Staphylococci (MRCoNS) isolates were hospital acquired and they showed 20% inducible clindamycin resistance. Our study shows the increasing prevalence of inducible clindamycin resistance among Methicillin resistant Staphylococcal isolates and denotes that D test should be carried out routinely in all laboratories.